Pakistan : Second, Third, Fourth, and Fifth Reviews Under the Extended Arrangement Under the Extended Fund Facility and Request for Rephasing of Access-Press Release; Staff Report; Staff Supplement, and Statement by the Executive Director for Pakistan. (IMF Staff Country Reports; Country Report, 2021)
While the Covid-19 shock temporarily disrupted Pakistan's progress under the program supported by the IMF's Extended Fund Facility (EFF), the authorities' policies have been critical in supporting the economy and saving lives and livelihoods. Aside from health-related containment measures, their response included a temporary fiscal stimulus, large expansion of social safety nets, monetary policy support, and targeted financial initiatives. These measures, supported by sizable emergency financing from the international community, including under an RFI, helped contain the first Covid-19 wave of cases and the impact on the economy. Growth slowed to -0.4 percent in FY 2020 (July-June), but is expected to recover to 1.5 percent in FY 2021. The external position improved, and inflation continued to decelerate through early 2021 despite supply-driven spikes in food prices. However, a second Covid-19 wave is unfolding, triggering exceptionally high uncertainty and downside risks.